Single- and multiple-dose tolerability, safety, pharmacokinetics, and pharmacodynamics of the dual endothelin receptor antagonist aprocitentan in healthy adult and elderly subjects - Sidharta PN; Melchior M; Kankam MK; Dingemanse J (Dove Medical Press, 2019)
Patricia N Sidharta,1 Meggane Melchior,1 Martin K Kankam,2 Jasper Dingemanse1 1Department of Clinical Pharmacology, Idorsia Pharmaceuticals Ltd, Allschwil CH-4123, Switzerland; 2Vince and Associates Clinical Research, Overland Park, KS 66211, USA Background: Aprocitentan is an orally active, dual endothelin (ET) receptor antagonist developed for the treatment of hypertension in which, despite available treatments, a medical need exists for drugs with a new mechanism of action. Subjects and methods: In this study, the single- and multiple-dose tolerability, safety, pharmacokinetics (PK), and pharmacodynamics of up to 600 mg (single doses) and 100 mg once a day (qd; multiple doses) of aprocitentan were investigated in healthy male and female subjects. The effect of age on the tolerability and PK parameters was investigated at a dose of 100 mg qd.Results: Aprocitentan was well tolerated across all doses. No serious adverse events (AEs) occurred. The most frequently reported AE was headache. Small increases in body weight were recorded in subjects receiving 100 mg qd. Plasma concentration–time profiles of aprocitentan were similar after single- and multiple-dose administration, and support a qd dosing regimen based on a half-life of 44 hours. After multiple doses, PK was dose proportional. Accumulation at steady state, reached by Day 8, was 3-fold. Only minor differences in exposure between healthy females and males, healthy elderly and adult subjects, and fed and fasted conditions were observed. Plasma ET-1 concentrations, reflecting ETB receptor antagonism, significantly increased with doses ≥25 mg. Time-matched analysis of electrocardiogram (ECG) parameters did not suggest drug-induced ECG effects. Exposure–response analysis indicated no QTc prolongations at plasma levels up to 10 µg/mL. Conclusion: Aprocitentan was well tolerated in healthy subjects with a PK profile favorable for qd dosing. Keywords: first-in-human study, endothelin, endothelin receptor antagonist, aprocitentan, pharmacokinetics, pharmacodynamics